(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Vellarugu Enicostemma littorale Blume (E. littorale) (Gentian family) is a highly nutritious perennial medicinal plant and used as a medicine in Siddha Medical System to treat several disease conditions such as diabetes mellitus, rheumatism (Vata diseases), skin diseases (Pitta diseases), constipation, abdominal ulcers, swelling, obesity and insect poisoning. It is a rainy season herb, growing on moist, damp and shady ridges and slopes of the borders of cultivated fields and widely distributed in India, Eastern and Southern Africa, South America, and Asia. Whole plant, Leaves, Flowers, stem and Roots are mostly used for the treatment. Although there are numerous scientific studies related to multiple usage of Vellarugu plant, this study attempts to collect all available information and prepare a monograph about the E. littorale for documentation purpose. E. littorale has a number of anti-oxidative phytochemicals which include five alkaloids, catechins, saponins, two sterols, triterpinoids, phenolic acid, flavonoids, xanthones and volatile oil, swetiamerin, and gentianine. Higher percentage of total ash, water soluble ash and acid insoluble ash also were found in this plant. E. littorale has very low toxicity and is a safe and the presence of heavy metals was below the WHO/FDA permissible limits. Numerous studies stated that E. littorale has the therapeutic pharmacological actions such as anti-diabetic, antioxidant, hypolipidaemic, hepatoprotective, anti-inflammatory, analgesic, anti-arthritic, anti-microbial, anti tumour, and etc. This monograph may provide and confirmed the documentary evident for multiple medicinal and therapeutic uses and pharmacological effects of the E. littorale.